Bombay going : Nepali migrant sex workers in an anti-trafficking era - Åsman, Susanne (Lexington Books, 2018)
With a focus on women's agency, Susanne Åsman provides an ethnographic account of how Tamang women and men in the Sindhupalchowk district, defined as severely affected by sex trafficking, understand what they describe as Bombay going or migration for sex work.